A formação do educador do PROEJA do IFPB / Campus de Cajazeiras. - Silva, Maria José Marques (2010)
The purpose of this study is to analyse the education of teachers who work in the National Program of Integration of Vocational Education with Basic Education in the form of Young and Adults PROEJA, in the Federal Institute of Education, Science and Technology/Campus Cajazeiras, It also seeks to highlight the problem of teacher education in Brazil, as well as to contextualize the implementation of PROEJA on the national scenery and in our research context and to describe the social and cultural profile of the teachers who take part in the research, to identify the difficulties experienced by the teachers working in the PROEJA, in IFPB Campus Cajazeiras, in what regards to their education. For this, we attempted to discuss the current issues involving the national debate about Young and Adult Education in our country, among which is one of the major concerns in the field of Young and Adults Education (EJA), which refers to the specific characteristics of students of EJA and consequently also requires a teacher specific education that can meet the particularities of those who try to get back to their studies. The research was characterized as an exploratory descriptive study based on queitative approach. As data collection techniques, we used field observations, semi-structured interview, socio-cultural form, as well as the official documents which support the PROEJA and the internal project of the course. It was found that there is a gap between the school and the requirements established in the guidelines given for implementation of PROEJA. This detachment is due to the lack of a better monitoring of the program within the institution (it even lacks a coordinator for the PROEJA, among other things), but also to the absence of a more systematic monitoring by the regulatory institutions, and yet because the civil society does not know how to assert their rights. We understand that the supply of High School integrated to Vocational Education in the mode of EJA demands a restructuring of educational practices, which may promote the transformation of our society.